Targeting BCMA in multiple myeloma: designs, challenges, and future directions - Hu, Yi; Xie, Yuetao; Wang, Xiaodong; Yang, Lufeng; Geng, He; Yi, Zugang; Zhang, Yao; Ma, Lin; Chen, Fang (Cancer Immunology, Immunotherapy : CII, 2025)
Chimeric antigen receptor (CAR) T cell therapy has emerged as a groundbreaking immunotherapy, demonstrating significant efficacy in treating B cell malignancies. In the context of multiple myeloma (MM), B cell maturation antigen (BCMA) has been identified as a critical target, driving the development of CAR T cell therapies designed to address this plasma cell cancer. Various CAR designs, utilizing different BCMA recognition domains, have yielded promising clinical results, leading to the approval of two BCMA-targeting CAR T cell therapies by the US Food and Drug Administration (FDA) for the treatment of MM. This review uniquely examines the BCMA CAR T cell landscape, emphasizing the design of recognition domains, clinical efficacy, and patient outcomes. It critically addresses emerging challenges such as antigen escape and toxicity profiles, which have surfaced alongside therapeutic advances. Moreover, the review spotlights cutting-edge developments, including dual-targeting CAR T strategies, advancements in CAR T cell manufacturing, and innovative allogeneic CAR T approaches utilizing healthy donor cells. By detailing both the breakthroughs and ongoing challenges in BCMA CAR T cell therapy, this review offers a comprehensive perspective on the current state and future possibilities of CAR T cell therapy for MM and its expanding role in treating hematologic malignancies and beyond.